The Development of IPS Moduleas Base of interactive Multimedia for Students at Grade IV in Elementary School - Madona, Ade Sri; Nora, Yulfia (Jurnal Pelangi : Research of Education and Development, 2016)
IPS is a knowledge which sustained many kinds of disciplinary knowledge and the humanities. It also includes human activities covers as scientific which purpose to give knowledge and comprehension for students in Elementary School. Teaching IPS must be interesting for students in order, they comprehend all of the materials easily. Therefore, it is necessary to create module of learning IPS as base of Interactive multimedia for students at grade IV in Elementary school.            The methodology of this research is development research. This research purposes to develop and create a new product in learning system which will be applied for Elementary students.            The result of this research was the average of multimedia instrument validation 3,40 which category as valid. The result of the practice testing from students responded during teaching learning was very practically which average 3,67 in category appropriate. The result of teacher responded for practicality of IPS module was practice which average 3,38. From observation of students activities in one meeting was in high category which average 71,15. Then, the result of observation during disseminate showed that the activities of students includes in high category which average 68,33. It can be concluded that module of learning interactive multimedia good in all of learning activities.